The creation and characterization of the bread wheat line with a centric translocation T2DL.2RL - Yu. N. Ivanova; L. A. Solovey; D. B. Loginova; E. E. Miroshnikova; N. I. Dubovets; O. G. Silkova (Вавиловский журнал генетики и селекции)
The development of bread wheat introgressions with alien genetic material from cultural and wild Triticeae species is an effective method for expanding the wheat gene pool necessary for breeding. To date, numerous collections of introgressions as substitutions and chromosome modifications have been obtained; however, the creation and study of wheat with new valuable traits still remain an important line of research. Rye Secale cereale L., whose chromosomes carry genes that control valuable economic and biological characteristics and properties, is widely used to produce new wheat forms. In this study, a wheat-rye translocation obtained by backcrossing the wheat-rye disomic-substitution line 2R(2D)1 with the variety Novosibirskaya 67 was characterized. The chromosomal composition of karyotypes was studied using fluorescent in situ hybridization and C-banding. Two centric translocations, derived from two long arms of chromosomes 2D and 2R, T2DL.2RL, were identified, the remaining 40 wheat chromosomes did not undergo modifications. Meiosis in the lines was stable. Chromosomes T2DL.2RL formed bivalents in all meiocytes, which confirmed their homology. The morphological characteristics of the spike in the T2DL.2RL line and Novosibirskaya 67 did not differ. A comparative analysis of productivity between the T2DL.2RL translocation line and the parental forms, Novosibirskaya 67 and the 2R(2D)1 line, was carried out. The T2DL.2RL line is inferior to Novosibirskaya 67 in all characters with different confidence levels. The productivity characters of the 2R(2D)1 line exceeded or did not differ from those of T2DL.2RL, however, the mass of 1000 grains was significantly lower. The results showed the effect of the T2DL.2RL translocation on the trait “plant height”. This character was significantly lower than that of Novosibirskaya 67 in two vegetation periods. Consequently, the T2DL.2RL translocation reduces plant height and productivity.